PALEOANTHROPOLOGY OF EASTERN MONGOLIA - D.TUMEN (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2023)
During archaeological fieldworks carried out in 2002-2003 several unknown before to scientists archaeological sites, belonging to different historical periods (from Bronze up to Mongolian Period) were discovered at Tsuvraa Uul and Bayan-Uul mountain areas in Khulenbuir sum, Dornod aimag. Around 30 graves dated to Hunnu and Mongolian periods were excavated in the site and some significant archaeological findings and well preserved human remains were unearthed. The aims of the paleoanthropological study are 1) To carry out craniological studies of human remains yielded from archaeological excavations in Eastern Mongolia, 2) To conduct comparative morphological analysis of ancient populations from Eastern Mongolia and Northeast Asia based on the obtained craniofacial data, to test the biological and historical relationships of the studied prehistoric populations from Eastern Mongolia and Northeast Asia. Cranial series used in the comparative research encompass 21 Neolithic samples, 26 Bronze and Early Iron samples and 14 Hunnu samples from Inner Asia. Fifteen cranial variables (five for the neurocranium, and ten for the facial skeleton) were defined by Martin (1928), V.P. Alexseev and G.F. Debets (1961) and W.Bass (1987) methodics and provided the metrical basis for the current study. The comparative study was conducted separately for each historical period. Penrose shape distances were calculated between each pair of compared populations. The main upshot of the paleoanthropological studies of the prehistoric populations from Eastern Mongolia is the following: generally, prehistoric populations from Eastern Mongolia is characterized with mongoloid anthropological features with an exception of the Hunnu population which is not anthropologically quite homogeneous. It may be explained by extensive migration of nomads from Eurasian steppe (Caucasoid or mixed populations from west to east and Mongoloids from East to West) lasted throughout the Bronze and Early Iron Age and Hunnu period in Inner Asia. This fact may show close genetic and biological relationships between Neolithic population from Eastern Mongolia, Bronze age populations with slab grave culture from Central and Eastern Mongolia, Hunnu. Early Mongolian, Mongolian period and contemporary populations of Mongolia.